Self-esteem in oral expression - Garcia-Conislla, Julia E. (2023)
This research work focused on determining the relationship between self-esteem and oral expression of the students of the Faculty of Education of the Universidad Nacional Mayor de San Marcos (UNMSM). The objective was to analyze how students' self-esteem affects their ability to speak. A basic type methodology was used, specifically a non-experimental design of causal level, since a causal relationship is identified between the variables studied. The technique used to collect data was the survey, through an instrument designed to assess both self-esteem and oral expression. The sample consisted of a total of 90 students, randomly selected during the period from July to August 2022. The results obtained from the investigation showed a significant p value (p < 0.05), specifically a p value equal to 0.000. Consequently, the null hypothesis was rejected and the alternative hypothesis was accepted, indicating that there is a significant relationship between self-esteem and oral expression. In other words, it was observed that higher self-esteem is related to better oral expression. The methodology used in this study is basic, non-experimental design at the causal level, because one of the variables affects the other. The technique used was the survey, using an instrument to capture both self-esteem and oral expression. The sample was made up of 100 students, the sample size chosen was considering 50% of the total number of students of the Faculty of Education of the specialty of Primary and Initial Education and represents a significant number to determine the information of the students with respect to their self-esteem and its relationship with oral expression. The sampling was carried out by random selection with the students who attend the Faculty of Education of the specialty of Primary and Initial Education during the period between July and August 2022.           The main results of the research is the existence of a significant positive incidence of self-esteem in oral expression, in this way the optimal development of these skills is essential to increase the levels of Teaching Performance and thus improve the quality of Education. in Peru.